Partial Transvenous Coil Embolization with Significant Clinical Improvement in Patient with Indirect Carotid Cavernous Fistula - Muh. Wildan Yahya; Achmad Firdaus Sani; Dedy Kurniawan; Mohammad Saiful Ardhi (Universitas Airlangga, 2022)
Highlight: CCF is a rare vascular malformation with challenging management. Partial transvenous embolization is quite effective as an alternative therapy for indirect CCF type D. ABSTRACT Introduction: An indirect carotid-cavernous fistula (CCF) is an abnormal connection between the internal or external carotid artery and the cavernous sinus. The optic, trochlear, abducens, and trigeminal nerves are located in the cavernous sinus. Head Computed Tomography (CT) scan, Magnetic Resonance Imaging (MRI), and Cerebral Angiography are some imaging modalities used to establish and diagnose carotid-cavernous fistula. Endovascular intervention can be performed with trans-arterial or trans-venous access. In some cases, complete embolization by endovascular treatment is not possible because of difficult angioarchitecture. Case: A 61-year-old female reported having pain in her left eye (numerical rating scale was 6). The left eye was bulging, reddish, ptosis, and unable to move. The patient felt double vision when opening both eyes, complained of intermittent stabbing headaches on the left side, and heard a bruit from the left side of the head. The cerebral angiography showed bilateral indirect CCF Barrow type D. The procedure involved partial transvenous embolization with coiling. The angiographic evaluation showed partial occlusion, and residual flow from the fistula was still visible on angiography. There was a significant clinical improvement several days after the procedure and a five-month follow-up. Conclusion: This case report showed that partial targeted transvenous embolization is quite effective in indirect CCF when complete embolization is impossible.